2008
DOI: 10.1111/j.1600-0838.2007.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular adaptations of voltage‐gated sodium ion channel related proteins after fatiguing stretch‐shortening cycle exercise

Abstract: Dystrophin associated protein alpha-syntrophin is known to interact with voltage-gated sodium ion channel (NaCh). Dystrophin is known to be sensitive to eccentric muscle actions. For this reason, the function of the NaChs might also be affected. Molecular adaptations of dystrophin, alpha-syntrophin and NaChs were investigated after fatiguing stretch-shortening cycle (SSC) exercise, which consisted of unilateral jumps on a sledge apparatus. Muscle biopsies were taken from the vastus lateralis muscle of eight he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Subjects performed less jumps compared to other maximally exhaustive SSC exercise investigations (Kuitunen et al, 2004;Piitulainen et al, 2008). In the present study, subjects ceased jumping upon volitional fatigue or if they could not maintain a rebound height of 50% of maximal, whereas subjects previously (Kuitunen et al, 2002(Kuitunen et al, , 2004Nicol et al, 2003;Dousset et al, 2007;Piitulainen et al, 2008) continued rebounding until they "were completely exhausted so that they were unable to jump off the force plate of the sledge" (Kuitunen et al, 2004). While such fully exhaustive protocols are recommended to reduce intersubject variability in fatigue (Nicol et al, 2006), they rarely occur in sporting environments and thus we deemed it not practically applicable to use such a protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjects performed less jumps compared to other maximally exhaustive SSC exercise investigations (Kuitunen et al, 2004;Piitulainen et al, 2008). In the present study, subjects ceased jumping upon volitional fatigue or if they could not maintain a rebound height of 50% of maximal, whereas subjects previously (Kuitunen et al, 2002(Kuitunen et al, , 2004Nicol et al, 2003;Dousset et al, 2007;Piitulainen et al, 2008) continued rebounding until they "were completely exhausted so that they were unable to jump off the force plate of the sledge" (Kuitunen et al, 2004). While such fully exhaustive protocols are recommended to reduce intersubject variability in fatigue (Nicol et al, 2006), they rarely occur in sporting environments and thus we deemed it not practically applicable to use such a protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Exhaustive SSC exercise on a sledge apparatus has previously been shown to significantly increase muscle soreness that remains elevated for at least 48 h (Nicol et al, 2003;Piitulainen et al, 2008). Studies that have compared CON and CWI after SSC exercise have found that active muscle soreness is increased for both groups at both 24 and 48 h after single (Leeder et al, 2015;Vieira et al, 2016;Anderson et al, 2018;Ahokas et al, 2019) and multiple (Howatson et al, 2009) immersions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation